2012
DOI: 10.1258/ebm.2012.012051
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal testosterone exposure as a model for the study of endocrine-disrupting chemicals on the gerbil prostate

Abstract: The development of the prostate depends on a precise androgenic control, so sensible interferences may predispose this gland to develop prostatic diseases during life. These aspects are of interest and preoccupation, since human beings are exposed to a growing number of endocrine-disrupting chemicals with androgenic potential. Therefore, our aim was to evaluate the prostates of adult gerbils exposed to testosterone during intrauterine life. Serological, morphological, morphometric-stereologic, immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Exposure to high doses of testosterone during the prenatal period decreases the immunoreactivity of p63 in regions with PIN in the ventral male prostate of the adult gerbil (Biancardi et al . ). Even when using low doses, we noted that exposure to DE during development is enough to cause neoplastic lesions and the loss of the basal cell layer in the ventral male prostate in the senile stage.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Exposure to high doses of testosterone during the prenatal period decreases the immunoreactivity of p63 in regions with PIN in the ventral male prostate of the adult gerbil (Biancardi et al . ). Even when using low doses, we noted that exposure to DE during development is enough to cause neoplastic lesions and the loss of the basal cell layer in the ventral male prostate in the senile stage.…”
Section: Discussionmentioning
confidence: 97%
“…; p63 protein (basal cell marker; mouse monoclonal IgG2a, 4A4: sc‐8431; Santa Cruz Biotechnology) (Biancardi et al . ), androgen receptor (AR; rabbit polyclonal IgG, N‐20: sc‐816; Santa Cruz Biotechnology) (Santos et al . ), oestrogen receptor‐alpha (ERα; rabbit polyclonal IgG, H‐184: sc‐7207; Santa Cruz Biotechnology) and oestrogen receptor‐beta (ERβ; rabbit polyclonal IgG, H‐150: sc‐8974; Santa Cruz Biotechnology) (Rochel‐Maia et al .…”
Section: Methodsmentioning
confidence: 99%
“…In rats, the complete prostate development encompasses five sequential events, which involve determination, initiation and budding, branching morphogenesis, differentiation, and maturation (Prins and Putz, ). The formation of a normal adult prostate depends on the exact occurrence of these events, so that sensible interferences may disrupt normal prostate development, affecting the formation of an adult normal prostate in terms of either architecture establishment or prostatic lesion development (Biancardi et al, ; Bruni‐Cardoso et al, ; Schaeffer et al, ; Timms, ). Taking this into account, efforts have been made to improve knowledge related to prostate development, which may be a determinant in defining the mechanisms underlying prostate disease physiology (Huang et al, ; Ousset et al, ; Wu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several works have been carried out by our research group employing the Mongolian gerbil ( Meriones unguiculatus ) as an experimental model in prostate studies involving drugs and hormonal manipulation (Biancardi et al, ; Corradi et al, ; Perez et al, ). However, the biology of prostate organogenesis of this species remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…; Biancardi et al . ), the present study opens new frontiers in research of the effects of oestrogenic chemicals on female prostate glands. These results have clinical relevance, as several studies have demonstrated the occurrence of Skene's paraurethral glands lesions in young and senile women (Sloboda et al .…”
Section: Discussionmentioning
confidence: 57%